Remzi Oğuz Arık and cultural nationalism in Turkey - Bülbül, Özlem. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2006., 2006)
Taking into consideration the historical development of nationalism in Turkey, it is not possible to claim that it followed a unique path. In fact, considering nationalism on the axis of Turkey needs in a way to take into account the intellectual accumulation these different perspectives put forward. At this point, cultural nationalism indicates an entirety of intellectual standings which are undeniable. The historical agenda of Turkey is rich with the cultural nationalist discourse that signified culturally extensive ideas on the basis of nationalism. Anatolia has been host to many nationalist discourses from the late era of the Ottoman Empire until today. The Anadoluculuk Movement, or Anatolian Nationalism, played a significant role in the historical development of one of the nationalist discourses, cultural nationalism. Within the Anadoluculuk Movement were three succeeding intellectual waves. This thesis concentrates on the second wave of the Anadoluculuk Movement throughout the 1930s and especially 1940s, the years that symbolized the golden age of nationalist currents in Turkey, and nationalist understanding of Remzi Oğuz Arık, who became a significant representative of this school of thought.
Keywords: Nationalism -- Turkey.; Culture.